2012
DOI: 10.1021/cm300749w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Changes in Voltage and Structure of Li2FeSiO4 Polymorphs for Lithium-Ion Batteries

Abstract: ABSTRACT:The search for new low cost, safe, and high capacity cathodes for lithium batteries has focused attention recently on Li 2 FeSiO 4 . The material presents a challenge because it exhibits complex polymorphism, and when it is electrochemically cycled there is a significant drop in the cell voltage related to a structural change. Systematic studies based on density functional theory techniques have been carried out to examine the change in cell voltages and structures for the full range of Li 2 FeSiO 4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 37 publications
11
130
0
Order By: Relevance
“…36), were obtained between the first and second discharge cycles which would indicate that no major structural change occurred following the initial charge. Such changes are a dominant feature of Li2FeSiO4 electrodes, where stable cycling is only achieved after cation rearrangement to a stable phase and have been outlined in various reports [498,500]. XRD studies of cycled cells revealed that structural change occurred after the first charge cycle leading to the formation of a new, seemingly metastable phase.…”
Section: Transition Metal Silicates (Li2msio4)mentioning
confidence: 82%
See 1 more Smart Citation
“…36), were obtained between the first and second discharge cycles which would indicate that no major structural change occurred following the initial charge. Such changes are a dominant feature of Li2FeSiO4 electrodes, where stable cycling is only achieved after cation rearrangement to a stable phase and have been outlined in various reports [498,500]. XRD studies of cycled cells revealed that structural change occurred after the first charge cycle leading to the formation of a new, seemingly metastable phase.…”
Section: Transition Metal Silicates (Li2msio4)mentioning
confidence: 82%
“…Fe, Mn or Co have typically been utilised, with more attention recently devoted to Li2FeSiO4 structures, due in part to reasons of safety and cost. The structure of Li2FeSiO4 has been a focus of a number of recent studies owing to its rich display of polymorphism [494][495][496][497][498][499], where a number of different polymorphs, designated as βI, βII, γ0, γII and γs (see Fig. 35), have been identified and account for an experimental variation in the electrochemical performance of Li2FeSiO4 cathodes [498][499][500].…”
Section: Transition Metal Silicates (Li2msio4)mentioning
confidence: 99%
“…Such DFT+U methods have been applied successfully to studies of other lithium battery materials. 52,59 3. DILUTE LI-ION AND NA-ION INTERCALATION:…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by renewed interest in β-MnO 2 , we performed an ab initio study of its intercalation behavior extending our recent computational work on lithium battery materials. 21,22 Of key interest is how mesoporous structuring enables intercalation into β-MnO 2 . Indeed, the rapidly growing interest in nanostructuring of many electrode materials 23,24 calls for investigation of the influence of surfaces and interfaces.…”
Section: ■ Introductionmentioning
confidence: 99%